PENINGKATAN PEMAHAMAN TATA KELOLA BLUD PUSKESMAS PANDAN - Firmanto, Yuki; Novianti, Nurlita (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract In accordance with Permendagri Number 79 of 2018, Pandan Health Center as a BLUD must implement a flexible financial management pattern based on Government Accounting Standards which is marked by the presentation of annual financial reports. Business and Budget Plans (RBA) and Standard Operating Procedures (SOPs) need to be prepared and presented economically, transparently and effectively in order to support the achievement of local government goals. The method of implementing community service uses the service learning method which has four stages, namely investigation, preparation, action and reflection. The results of the service show that the assistance in the preparation of the RBA shows good performance accompanied by the successful preparation of the opening balance of financial statements for 2022 and accounting policies together with the management of the BLUD. Details of the design of the Shopping SOP and Pharmacy SOP are also made and implemented taking into account the characteristics and business schemes of BLUDs in accordance with generally accepted regulations. In its implementation, the Pandan Health Center’s finances are expected to be able to understand and interpret financial statement analysis so that the objectives of the financial statements can be achieved more optimally. Abstrak Sesuai Permendagri Nomor 79 Tahun 2018, Puskesmas Pandan selaku BLUD mesti menyelenggarakan pola pengelolaan keuangan yang fleksibel berdasarkan pada Standar Akuntansi Pemerintah yang ditandai dengan adanya penyajian laporan keuangan tahunan. Rencana Anggaran Bisnis dan Anggaran (RBA) dan Standar Operasional Prosedur (SOP) perlu disusun dan disajikan secara ekonomis, transparan dan efektif demi menunjang pencapaian tujuan pemerintah daerah. Metode pelaksanaan pengabdian masyarakat menggunakan metode service learning yang terdapat empat tahapan yaitu investigasi, persiapan, tindakan dan refleksi. Hasil pengabdian menunjukkan bahwa pendampingan penyusunan RBA menunjukkan kinerja yang baik disertai dengan berhasil dibuatnya saldo awal laporan keuangan tahun 2022 dan kebijakan akuntansi bersama-sama dengan manajemen BLUD. Rincian desain SOP Belanja dan SOP Farmasi juga dibuat dan diimplementasikan dengan mempertimbangkan karakteristik dan skema bisnis BLUD sesuai dengan peraturan yang berlaku umum. Dalam pelaksanaannya, pihak keuangan Puskesmas Pandan diharapkan untuk mampu memahami dan menginterpretasikan analisis laporan keuangan supaya tujuan laporan keuangan dapat dicapai lebih optimal.